Groin hit death due to femoral vein rupture in a drug abuser - Shrestha, Kaschev; Poudel, Bipin; Ghimire, Pradeep; Parajuli, Aastha (Journal of Patan Academy of Health Sciences, 2022)
Recreational drug use has become an imminent social and health problem throughout the world. Intravenous injection for drug misuse has been described in both the upper and lower limbs and is a major cause of millions of deaths each year; deaths are primarily due to fatal overdose and the trauma and infection caused by repeated injections. This paper presents an accidental death due to massive blood loss, which resulted from rupture to the right femoral vessel based on autopsy findings. In case of accidental injuries, a thorough medico-legal process, including death scene investigation, autopsy examination and toxicological analyses, are always necessary to determine the manner of death.